66‐1: Invited Paper: High Mobility Flexible 2D Multilayer MoS2 TFTs on Solution‐Based Polyimide Substrates. Issue 1 (2nd June 2017) - Hong, Seongin; Naqi, Muhammad; Jung, Uihyun; Liu, Na; Kwon, Hyuk-Jun; Grigoropoulos, Costas P.; Hong, Young Ki; Kim, Sunkook
Abstract : We report on Molybdenum disulfide (MoS2) based Transition metal dichalcogenides (TMDs) transistor as flexible/stretchable electronics with consistent carrier mobility, wide band‐gap and mechanical expanse by using polyimide (PI) flexible substrate. Transistors fabricated in the following experiment have worthy properties: a field‐effect‐mobility measured as 108.6 cm 2 V ‐1 s ‐1 and an (Ion /Ioff ) ratio obtained as 5×10 5 . Moreover, no deviations occurred under methodical cyclic bending tests with bending radius of curvature of 10 and 5mm. Overall in the malleable areas of flexible integrated circuitry fabrication, the stated electrical and mechanical consequences provide significant applications.